Nanny dearest - Collins, Flora (Mira, 2021)
"Sue Keller is lost. When her father dies suddenly, she's orphaned in her mid-twenties...Then Sue meets Annie. It's been twenty years...She was Sue's live-in nanny at their big house upstate, and she loved Sue like she was her own...Sue is only too eager to welcome Annie back into her life; but as they become inseparable once again, Sue starts to uncover the truth about Annie's unsettling time in the Keller house all those years ago, particularly the manner of her departure--or dismissal"--